The Use of Documentary Video-Based Digital Media in Improving Students Interest in Learning History at SMA Negeri 2 Balaesang - Sarni Wulandari; Charles Kapile; Mutawakkil; Misnah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The development of digital technology in education has encouraged teachers to adopt innovative learning media to enhance students’ interest in learning, particularly in history subjects, which are often perceived as monotonous and less engaging. This study aimed to examine the utilization of documentary video-based digital media in improving students’ interest in learning history at SMA Negeri 2 Balaesang. The study employed a descriptive qualitative approach, focusing on an in-depth understanding of the implementation of documentary video media in history learning for grade XI students. Data were collected through observation, interviews, and documentation, then analyzed inductively to interpret the meaning of the findings. The results revealed that the use of documentary videos significantly increased students’ interest in learning history by presenting historical events in a more concrete, contextual, and engaging manner through audiovisual elements. Students demonstrated greater enthusiasm, improved understanding of historical concepts, and increased participation in discussions and learning activities. Teachers utilized documentary videos through systematic stages, including content selection, introductory explanation, video screening, reflective discussions, and evaluation activities. However, several challenges were identified, including limited technological infrastructure, unstable internet connectivity, time constraints, and varying levels of students’ visual literacy. Despite these obstacles, teachers remained committed to integrating documentary videos as an effective digital learning medium. In conclusion, documentary video-based digital media contributed positively to increasing students’ interest in learning history and created a more interactive, meaningful, and student-centered learning environment.